تصميم طريق يربط بين جامعة الشيخ عبدالله البدري والميناء البري - عبدالغني دفع السيد عبدالغني محمدين; محمد عثمان عباس رحمة; محمد ناجي محمد خليفة (جامعة الشيخ عبدالله البدري, 2023)
يهدف هذا البحث لتصميم هندسي لطريق يربط بين جامعة الشيخ عبدهللا البدري والميناء البري ولقد تمت دراسة عدة مسارات واجريت عليها العديد من المقارنات الختيار المسار االمثل والذي يحقق كفاءة في النقل واعلى خدمة في المنطقة واقل تكلفة واجري عليها حصر مروري باتباع طريقة الحصر اليدوي وتم اجراء الميزانية mالهندسية لتحديد شكل القطاعات وكان حجم المرور اليومي .48 day/veh. عرض الطريق = 5.7m طول الطريق =8.2 m عرض الكتفة = 5.7m حجم الردم= 3567.61 = حجم الحفر 88.2 3 السرعة التصميمة =03s/m مسافات الرؤية 2.: mمسافات الرؤيا للتوقف =52..65m مسافة الرؤية للتقاطعات =73 M المنحنيات -: طول المنحنى =73.8 ارتفاع ظهر المنحن = 3.5m 𝐷1 = 11𝑐𝑚 𝐷2 = 15.6𝑐𝑚 𝐷3 = 25𝑐𝑚 Abstract This research aims to design an engineering road linking Sheikh Abdullah Al-Badri University and the land port, and several paths have been studied and many comparisons have been made to choose the optimal path, which achieves efficiency in transportation and the highest service in the region and the lowest cost and conducted a traffic inventory by following the manual inventory method and the engineering budget was conducted to determine the shape of the sectors and the volume of traffic m and the width of the road 7.5 km and the length of the road 2.8 Veh/day 84 Lateral inclinations 1:2 and drilling volume backfill size = 16.564 Drilling size m^3= 2.2 Design speed = 30 m-stopping visibility distances =189.67 Sighting distances:89 MV Visibility Distance for Intersections =50 Curves:- Curve length = 50.2 mCurved back height = 0.7M with 1.5 shoulders